Modeling Sunflower Productivity and Profitability in Relation to Adequate and Limited Sulphur Availability under Semiarid Irrigated Conditions - Parvender Sheoran; O. P. Sheoran; Virender Sardana (International Journal of Agronomy)
Inadequate and/or imbalanced fertilization has been identified as one of the critical bottlenecks holding oilseeds production and productivity. Sustainable production requires efficient use of inputs maintaining optimum yield and high quality product. The present study aims at defining the quantitative relationship between the fertilizer S applied and the sunflower yield obtained using a polynomial function. The analysis was done to allocate the S fertilizer for maximization of net profit over fertilizer cost depending on the availability of the fertilizer. The results indicated that the cost effective economically optimum dose of sulphur for sunflower cultivation was found to be 36.70 kg S/ha under its full availability. The expected sunflower yield at this dose was worked out to be 2.619 t/ha. However, it is advisable to uniformly distribute the fertilizer to all over the cultivable area under its limited availability for exploiting the desired yield potential and maximum net monetary returns.